2013
DOI: 10.1177/1715163513492642
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist and physician views on collaborative practice

Abstract: Background: Strong working relationships between pharmacists and physicians are needed to optimize patient care. Understanding attitudes and barriers to collaboration between pharmacists and physicians may help with delivery of primary health care services. The objective of this study was to capture the opinions of family physicians and community pharmacists in Newfoundland and Labrador (NL) regarding collaborative practice. Methods: Two parallel surveys were offered to all community pharmacists and family p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 19 publications
2
34
0
4
Order By: Relevance
“…The preponderance of previous research has largely focused on exploring the relationship between community pharmacists and general practitioners [18][19][20][21][22][23][24][25], and also on primary care and inpatient settings [26][27][28]. A recent systematic review has highlighted the positive attitudes that pharmacy students, practicing pharmacists and faculty had towards Interprofessional Education (IPE) and IPC.…”
Section: Introductionmentioning
confidence: 99%
“…The preponderance of previous research has largely focused on exploring the relationship between community pharmacists and general practitioners [18][19][20][21][22][23][24][25], and also on primary care and inpatient settings [26][27][28]. A recent systematic review has highlighted the positive attitudes that pharmacy students, practicing pharmacists and faculty had towards Interprofessional Education (IPE) and IPC.…”
Section: Introductionmentioning
confidence: 99%
“…Self-report data suggests that most physicians receive less than four calls a day 1 , and that the advent of computer-generated prescriptions has reduced the number of interventions required by pharmacists 2 . Telephone calls remain the most preferred method of communication for pharmacists and prescribers, though pharmacists report wanting to explore electronic communication 3 . Barriers to high quality collaborative communication have been identified in focus groups with pharmacists and prescribers 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the common opinion of medical and pharmaceutical professionals is becoming more relevant in the process of providing appropriate assistance to patients and participation in reimbursement programs, a number of studies have been conducted to improve the above issues. Thus, in a study called «Pharmacist and physician views on collaborative practice», scientists concluded that collaborative practice could lead to improved patient outcomes and optimized compensation payments [16]. The authors of the article «Facilitating collaboration between pharmacists and physicians using an iterative interview process» ound that cooperation in medical and pharmaceutical care, including monitoring and adherence to the medication regimen, common practice agreements, to resolve issues related to service and compensation, and the mechanism of urgent communication [17].…”
Section: № 1(53) Vol1 January 2020mentioning
confidence: 99%